(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Childhood-onset idiopathic generalized epilepsies (IGEs) represent a heterogeneous group of genetically determined epileptic syndromes characterized by generalized seizure types and the absence of structural brain abnormalities. These disorders include a spectrum of syndromes such as benign myoclonic epilepsy of infancy, childhood absence epilepsy, epilepsy with myoclonic-astatic seizures, and epilepsy with myoclonic absences. This review provides a comprehensive analysis of their pathophysiology, clinical manifestations, electroencephalographic features, differential diagnosis, and treatment strategies. Although many forms exhibit favorable outcomes, certain syndromes demonstrate pharmacoresistance and neurocognitive impairment, emphasizing the importance of early diagnosis and individualized management.